Competition and entrepreneurs' human capital in small business longevity and growth. - Mengistae, Taye (Journal of Development Studies, 2006)
An analysis of data on a sample of small-scale manufacturers shows that a business is less likely to survive and grows slower the smaller the average price–cost margin in the industry in which it operates. The probability of survival is also smaller in import competing industries. So is the mean growth rate among survivors. We interpret this as evidence that small businesses are less likely to survive and grow slower in industries where the pressure of competition is stronger. Given competitive pressure and establishment characteristics, the probability of business survival and the expected growth rate conditional on survival both increase with entrepreneurial human capital. This is in the sense that the probability of business survival increases with the number of years of schooling and the number of years of business experience of the entrepreneur as does the expected growth rate conditional on survival. These results are consistent with another finding that unobservable influences on business hazard are correlated with those on growth. As a result, the effect of competition and entrepreneurial human capital on the growth of survivors would be biased for the effect of the same variables on the expected growth rate of a startup.